REVIEW ARTIKEL: NANOPARTIKEL PERAK TERMODIFIKASI L-Cysteine UNTUK ANALISIS ION LOGAM BESI(II) - Wijayanti, Alvina Nuril; Alimuddin, Alimuddin; Arif, Moh. Syaiful (PROSIDING SEMINAR KIMIA, 2024)
Silver nanoparticles are silver metal with nano size (<100 nm). Silver nanoparticles are widely researched because they have wide applications in everyday life. The method often used to synthesize silver nanoparticles is the bottom-up method. The principle of this method is the reduction reaction of Ag+ ions to Ag0, which is in the form of silver nanoparticles. Based on the literature, the selection of an appropriate reducing agent greatly influences the size and stability of the resulting nanoparticles. Highly reactive reducing agents that are often used include: ascorbic acid, trisodium citrate and sodium borohydrate. Modification of silver nanoparticles using L-Cysteine functions as a capping agent/stabilizer which has been proven to be stable for up to 3 months. Silver nanoparticles modified with L-Cysteine function as a chloramphenicol sensor, which is characterized by a color change from yellow to brown. This color change occurs due to the aggregation of silver nanoparticles which is triggered by the interaction between silver nanoparticles and chloramphenicol. Keywords : Silver nanoparticles, L-Cysteine, capping agent.